Influence of ceramic Al2O3 particulates on performance measures and surface characteristics during sinker EDM of stir cast AMMCs. (16th July 2019) - Khajuria, Akhil; Akhtar, Modassir; Pandey, Manish Kumar; Singh, Mayur Pratap; Raina, Ankush; Bedi, Raman; Singh, Balbir
Abstract : Purpose: AA2014 is a copper-based alloy and is typically used for production of complex machined components, given its better machinability. The purpose of this paper was to study the effects of variation in weight percentage of ceramic Al2 O3 particulates during electrical discharge machining (EDM) of stir cast AA2014 composites. Scanning electron microscopy (SEM) examination was carried out to study characteristics of EDMed surface of Al2 O3 /AA2014 composites. Design/methodology/approach: The effect of machining parameters on performance measures during sinker EDM of stir cast Al2 O3 /AA2014 composites was examined by "one factor at a time" (OFAT) method. The stir cast samples were obtained by using three levels of weight percentage of Al2 O3 particulates, i.e. 0 Wt.%, 10 Wt.% and 20 Wt.% with density 1.87 g/cc, 2.35 g/cc and 2.98 g/cc respectively. Machining parameters varied were peak current (1-30 amp), discharge voltage (30-100 V), pulse on time (15-300 µs) and pulse off time (15-450 µs) to study their influence on material removal rate (MRR), tool wear rate (TWR) and surface roughness (SR). Findings: MRR and SR decreased with an increase in weight percentage of ceramic Al2 O3 particulates at the expense of TWR. This was attributed to increased microhardness for reinforced stir cast composites. However, microhardness of EDMed samples at fixed values of machining parameters, i.e. 9 amp current, 60 V voltage, 90 µs pulse off time and 90 µs pulse on time reduced by 58.34, 52.25 and 46.85 per cent for stir cast AA2014, 10 Wt.% Al2 O3 /AA2014 and 20 Wt.% Al2 O3 /AA2014, respectively. SEM and quantitative energy dispersive spectroscopy (EDS) analysis revealed ceramic Al2 O3 particulate thermal spalling in 20 Wt.% Al2 O3 /AA2014 composite. This was because of increased particulate weight percentage leading to steep temperature gradients in between layers of base material and heat affected zone. Originality/value: This work was an essential step to assess the machinability for material design of Al2 O3 reinforced aluminium metal matrix composites (AMMCs). Experimental investigation on sinker EDM of high weight fraction of particulates in AA2014, i.e. 10 Wt.% Al2 O3 and 20 Wt.% Al2 O3, has not been reported in archival literature. The AMMCs were EDMed at variable peak currents, voltages, pulse on and pulse off times. The effects of process parameters on MRR, TWR and SR were analysed with comparisons made to show the effect of Al2 O3 particulate contents.